National scientific literature on nursing ethics: a systematic Review - Ilka Nicéia D’Aquino Oliveira Teixeira; Liliana Maria Labronici; Maria de Fátima Mantovani (Revista Brasileira em Promoção da Saúde, 2010)
Objective: To identify the most prevalent nursing ethical issues published in scientific Brazilian journals. Methods: A systematic literature review with the following inclusion criteria: (1) articles on Nursing Ethics written in Portuguese, English, French, and Spanish; (2) published in Brazilian journals; (3) in the period from January 1997 to February 2009. The search was carried out in four databases BDENF, LILACS, MEDLINE, and SCIELO. The key-words were ethics AND nursing. The selected studies were classified into categories. The content of the articles were analyzed using the Collective Subject Discourse. The categories generated discourses by organizing the main excerpts from the abstracts of the selected studies, which are the “key expressions”. Results: A hundred and thirty three articles that met the inclusion criteria were classified into eight categories: 1. Nursing Care; 2. Dilemmas and Controversies; 3. Education; 4. Legal Aspects; 5. Research; 6. Management; 7. Values and Beliefs; 8. Perspectives and Health Policies. The category “Nursing Care” prevailed in 36% of the selected articles, and it was classified into six subcategories. “Dilemmas and Controversies” was the second most prevalent category (15%). Conclusion: The number of theoretical papers on ethical issues is high, but there is little research on the ethical experiences in nursing practice.